VD_FINDINFO Pron / 2011 / 130 vom 18. November 2011 - VD Tribunal cantonal (2011)
ORGANISATIONEN GÉNÉRAL, SOCIÉTÉ À RESPONSABILITÉ LIMITÉE, REGISTRE DU COMMERCE | 731b CO, 941a CO, 154 al. 3 ORC, 154 ORC